Efeitos deletérios ocasionados por sonda orogástrica em recém nascido a pré-termo em uma uti neonatal: relato de caso clínico (Research, Society and Development, 2020)
There are countless causes that lead a baby to be born premature: placental changes (placenta previa and premature detachment), excess amniotic fluid, maternal age (mothers under 18 years of age), maternal infections, primacy, use of alcohol and drugs. The premature baby's trajectory begins with hospitalization, usually for long periods in the Neonatal Intensive Care Unit (NICU), due to pulmonary immaturity and the need for prolonged ventilatory support. Gastric probing by oral or nasal route is an essential procedure in assisting nutrition for newborns up to thirty-four weeks of gestational age, as it does not have fully developed sucking and swallowing reflexes. The literature describes several oral changes present in premature and low birth weight children, highlighting an increase in the incidence of enamel defects, such as hypoplasia and hypomineralization, an increase in the incidence of dental caries, developmental and eruption delay of the primary dentition, dental and palate malformation. The aim was to report the clinical case of a premature infant with chronic use of an orogastric tube (OT) with lesion in the middle region of the upper lip and gum pad. After 24 hours of repositioning the OT, can be observed the lesion regression. Thus, the presence of the dentist in the NICUs, assisting with protocol and diagnostic measures, can minimize deleterious effects on the oral cavity. It should be noted that the training and applicability of dental protocols in NICUs improves safety in the care of the newborn.